2015
DOI: 10.1002/jsfa.7339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed moisture, extrusion temperature and screw speed on properties of soy white flakes based aquafeed: a response surface analysis

Abstract: SWF was used as an alternative protein source of fish meal. Our study shows that aquafeed with high durability, lower bulk density and lower water absorption and higher solubility indices can be obtained by adding SWF up to 40%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
4
27
0
1
Order By: Relevance
“…During extrusion, the raw materials undergo many chemical and structural transformations, thereby developing their textural properties, water retention capacity, digestibility and other functionalities . In previous studies, many groups have investigated the optimization of extrusion conditions for twin‐screw extruded barley flour, rice flour, pea protein isolates and soy protein isolates . In the case of wheat protein, Li and Lee investigated the effect of extrusion temperature on the solubility and molecular weight distribution of proteins in wheat flour and demonstrated that hydrophobic interactions and disulfide bond formation played a key role in wheat protein aggregation during twin‐screw extrusion.…”
Section: Introductionmentioning
confidence: 88%
“…During extrusion, the raw materials undergo many chemical and structural transformations, thereby developing their textural properties, water retention capacity, digestibility and other functionalities . In previous studies, many groups have investigated the optimization of extrusion conditions for twin‐screw extruded barley flour, rice flour, pea protein isolates and soy protein isolates . In the case of wheat protein, Li and Lee investigated the effect of extrusion temperature on the solubility and molecular weight distribution of proteins in wheat flour and demonstrated that hydrophobic interactions and disulfide bond formation played a key role in wheat protein aggregation during twin‐screw extrusion.…”
Section: Introductionmentioning
confidence: 88%
“…After centrifuge, the supernatant was transferred to a tarred aluminum cups and dried at 135°C for 2 hr to remove the moisture. The WAI and WSI were then calculated as mentioned by Singh and Muthukumarappan (2016).…”
Section: Water Absorption and Water Solubility Indicesmentioning
confidence: 99%
“…The organic macromolecules, namely, starch, protein, and fiber, undergoes chemical and physical transformation and new unique product emerges out of the extruder. The product quality depends on several factors such as the feed material, composition of the feed material, moisture content of the feed material, extruder type, screw configuration, screw speed, feed rate, and temperature of the barrel sections (Singh & Muthukumarappan, ; Singha, Muthukumarappan, & Krishnan, ). Other factors such as residence time, pressure and shear too influence the extrusion cooking of the food materials (Singh & Muthukumarappan, , ).…”
Section: Introductionmentioning
confidence: 99%